Impact of the 2008 economic and financial crisis on child health: a systematic review - Rajmil, Luis; Fernandez de Sanmamed, María-José; Choonara, Imti; Faresjö, Tomas; Hjern, Anders; Kozyrskyj, Anita; Lucas, Patricia; Raat, Hein; Séguin, Louise; Spencer, Nick; Taylor-Robinson, David (MDPI, 2014)
The aim of this study was to provide an overview of studies in which the impact of the 2008 economic crisis on child health was reported. Structured searches of PubMed, and ISI Web of Knowledge, were conducted. Quantitative and qualitative studies reporting health outcomes on children, published since 2007 and related to the 2008 economic crisis were included. Two reviewers independently assessed studies for inclusion. Data were synthesised as a narrative review. Five hundred and six titles and abstracts were reviewed, from which 22 studies were included. The risk of bias for quantitative studies was mixed while qualitative studies showed low risk of bias. An excess of 28,000–50,000 infant deaths in 2009 was estimated in sub-Saharan African countries, and increased infant mortality in Greece was reported. Increased price of foods was related to worsening nutrition habits in disadvantaged families worldwide. An increase in violence against children was reported in the U.S., and inequalities in health-related quality of life appeared in some countries. Most studies suggest that the economic crisis has harmed children’s health, and disproportionately affected the most vulnerable groups. There is an urgent need for further studies to monitor the child health effects of the global recession and to inform appropriate public policy responses.